(untitled) (Orfeu, 2023)
This text addresses politics and music at the beginning of the Republic of Brazil. The objects of study are the trajectory of two composers of the time: Leopoldo Miguéz and Alberto Nepomuceno. Both composers were convinced republicans and important directors of the National Institute of Music in Rio de Janeiro. The works addressed, Ave, Libertas! by Leopoldo Miguéz, and Série Brasileira by Alberto Nepomuceno express homage, commemoration, nationalism in music, and also express programmatic elements that are sometimes not explicit. Finally, the text proposes programs inferred from the musical structure for the works.